The Influence of Business Development of Fish Floating Cages on Tourism in Maninjau Lake, Tanjung Raya Sub-District, Agam Regency, West Sumatera Province - Everina, Silvia; Bathara, Lamun; AN, Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstrak The research was conducted in March 2017 located at Maninjau Lake, Tanjung Raya Sub-District, Agam Regency, West Sumatera Province. This study aims to determine the development trend of fish floating cages business and tourism development in Maninjau Lake and to know what objects are affected by fish floating cages business in Maninjau Lake. The method used in this study is survey method, where the determination of respondents to visitors and businessman using accidental sampling method. The result of this research have showed that the relationship between fish floating cages business trend with development of tourism is when fish floating cage began to increase every year showed a trend that increased significantly and otherwise tourism development in Maninjau Lake showed a declining trend. Tourism objects that are effected by fish floating cages business has an influence on income both before and after the development of fish floating cages. afforts that have been made by the govemment in the development of tourism in Maninjau Lake after the development of fish floating cages is to optimize the reduction the number of fish floating cages plots and continue to seek the formation of environmentally friendly fish floating cages. Keywords : Maninjau Lake, Fish floating cages, Tourism